Colonic perforation during laparoscopic hernia repair presented as delayed generalized subcutaneous emphysema: a clue to intra-abdominal complication - Hajhamad, Mohammed M.; Azman, Zairul Azwan; Rahman, Nur Afdzillah; Jailani, Ruhi Fadzlyana; Mazlan, Luqman; Sagap, Ismail (International Surgery Journal, 2016)
Laparoscopic operations are generally safe procedures. Complications of carbon dioxide (CO2) insufflation are rare but can be life threatening. That’s why it is very important for whoever handling this type of patients to be familiar with those complications and consequences. We are presenting a 61 year old woman who underwent laparoscopic repair of umbilical hernia. Surgery was uneventful; patient discharged home next day. Eight days later patient presented with generalized subcutaneous emphysema, started on the third postoperative day. CT scan showed extensive, generalized, subcutaneous emphysema with pneumomediastinum and penumoperitoneum. Laparotomy showed perforation at cecum, with gross faecal contamination of peritoneal cavity, right hemicolectomy with double barrel stoma performed. Colonic perforation may be due to thermal iatrogenic injury during surgery predisposed by presence of adhesions and diseased bowels as confirmed by histpathologic examination. We concluded that long operative time, higher CO2 pressure, more surgical ports and older age can be predisposing factors for this rare of presentation for colonic perforation.